Partisipasi Masyarakat dalam Mewujudkan Desa Mandiri di Desa Toapaya Selatan Kabupaten Bintan Tahun 2023 - Dyas Puzi Rahmadina (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Community-based village development serves as a crucial strategy to reduce regional disparities and enhance village self-reliance. However, among the 36 villages in Bintan Regency, only two were categorized as Independent Villages in 2023, one of which is Toapaya Selatan Village. This study aims to examine how community participation contributes to the achievement of Independent Village status in Toapaya Selatan. The research applied a descriptive qualitative method, with data collected through observation, interviews, and documentation involving 15 informants. The findings reveal that community participation occurred actively across four key stages: decision-making, implementation, benefit-taking, and evaluation. In the decision-making process, residents were engaged through structured deliberations beginning at the neighborhood (RT) level and culminating in the village development planning meeting (Musrenbangdes). In the implementation stage, participation was reflected in both physical development projects and empowerment activities that fostered local capacity. The benefit-taking stage showed that residents equitably shared the outcomes of development through a system of regional rotation and principles of fairness. In the evaluation stage, the community was provided with both formal and informal spaces to voice aspirations and feedback, ensuring accountability and inclusiveness in governance. Despite the relatively high level of participation, several challenges persisted, including the dominance of representative systems, which limited direct involvement of broader community members, and the need for stronger capacity-building efforts. These findings suggest that while Toapaya Selatan Village has successfully demonstrated the potential of community-based participation in achieving independent status, sustaining and replicating this success in other villages requires continuous strengthening of community capacity, more inclusive participatory mechanisms, and institutional support. Strengthening these aspects will not only enhance the quality of participation but also ensure sustainable development outcomes that can be applied as a model for other villages.